Given:  f(x) = 1/x-2    g(x) = the square root of x-3

Find  f(g(5))

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`f(x)=1/(x-2)` and `g(x)=sqrt(x-3)` 

To find `f(g(5))` plug in g(x) wherever x appears in f(x):

`therefore f(g(5))= 1/(sqrt(x-3)-2)`

As x=5 `therefore f(g(5))=1/(sqrt(5-3)-2)`

`therefore = 1/(sqrt2 - 2)`

To rationalize the denominator (ie remove the square root):

`= 1/(sqrt2-2) times (sqrt2+2)/(sqrt2+2)` Note that in essence it remains the same :

`therefore = (sqrt2+2)/(2-4)` The middle term has been eliminated

`therefore f(g(5))=(sqrt2+2)/-2`  or `-sqrt2/2+1` 


f(g(5))= `(sqrt2+2)/-2`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial